Use of Stand-Biased Desks to Reduce Sedentary Time in High School Students: A Pilot Study - Pickens, Adam W.; Benden, Mark E.; Schneider, Drew E.; Zhao, Hongwei (International Journal of Child Health and Nutrition, 2016)
Background: The purpose of this pilot study was to identify differences between sitting and standing time in high school students’ pre and post stand-biased desk intervention. Methods: ActivPal3™ activity monitors were affixed to 25 Bryan Collegiate High School students’ to monitor their standing time and activity levels. Data were collected at the beginning of the school year (fall) in traditional seated desks and in the spring in stand-biased desks. After attrition, 18 of the original 25 students were included in the final analysis. The physical activity data (steps) as well as standing and sitting time data provided by the monitors was used for within subject intervention analyses. Results: Descriptive statistics and a two-sided t-test were used to analyse differences between pre and post intervention sitting and standing times. Analysis indicated a significant reduction of sitting time post stand-biased desk intervention (p<0.0001) and a significant increase in standing time, post stand-biased desk intervention (p<0.0001). Analysis also revealed a non-statistically significant (p < 0.0619) average increase of 2,286 steps per school day when comparing mean steps pre-intervention (6,612) and post-intervention (8,898). Conclusions: Standing desks have the potential to reduce sedentary behavior and increase light to moderate physical activity for high school students during the school day.